Localization of Antigenic Sites in Unfed Nymphs of Amblyomma triste Koch 1844 (Acari: Ixodidae) Ticks by Immunohistochemistry - Otavio, F. M. S. [UNESP]; Bechara, Gervasio Henrique [UNESP]; Del Vecchio, R. E. [UNESP] (Wiley-Blackwell, 2010)
P>The reactivity of sera collected from guinea pigs after three infestations with Amblyomma triste nymphs on histological sections of the same tick species was investigated through immunohistochemistry to identify potential target cells and tissues. Six guinea pigs were infested thrice, at 30 day intervals, with 30 nymphs of A. triste per animal per infestation. Blood samples were collected from the guinea pigs 15 days after each infestation for serum separation; normal serum was obtained before the first infestation as control. Unfed A. triste nymphs' histological sections were submitted to indirect immunohistochemistry technique by using normal or hyperimmune guinea pig serum as primary antibody and a goat IgG-alkaline phosphatase-APase conjugate as secondary antibody. A weak to moderate APase activity was observed in cells of salivary glands, midgut and haemolymph of unfed nymphs incubated with hyperimmune serum.
Keywords: Immunohistochemistry; guinea pig; Amblyomma triste; unfed nymphs; antigenic sites